Biotransformation of chromium (VI) in liquid effluents by resistant bacteria isolated from the Matanza-Riachuelo basin, in Argentina - González, Ana Julieta (2017)
The aims of this investigation were to evaluate the bacterial resistance to zinc, copper, chromium (VI) and lead in surface water streams from Buenos Aires, Argentina; to select a chromium-resistant strain able to remove the metal in batch process and to evaluate the potential of this strain to remove chromium (VI) in liquid effluents. Bacterial resistance to the metals was evaluated by determining the minimal inhibitory concentration. The kinetic of chromium (VI) removal by one of the resistant strains was studied in nutrient broth with 50 and 100 mg L−1 of the metal, as well as an effluent from an electroplating industry. High resistance to all the metals under study was observed in the bacterial communities of the Matanza-Riachuelo basin. A chromium-resistant strain was isolated and identified as Microbacterium sp. It was able to remove 50 and 100 mg L−1 of Cr (VI) in 36 and 66 h respectively, with efficiency higher than 99%. Experiments with liquid effluents showed the ability of the strain to transform 150 mg L−1 of the metal in 84 h, with efficiency higher than 99%. These results show the potential of this native strain for the treatment of liquid effluents that contain chromium (VI).